Photoredox Defluorinative Silylation of α-Trifluoromethyl Arylalkenes Using Silacarboxylic Acids as Silyl Radical Precursors - Zhang, Yi; Nie, Guihua; Jin, Zhichao; Ren, Shichao (Synlett, 2023)
A photoredox defluorinative silylation of α-trifluoromethyl arylalkenes for rapid access to useful gem-difluoroalkenes is disclosed. Stable and easily prepared silacarboxylic acids are used as silyl radical precursors in a photocatalytic decarboxylative process. The mild conditions and operational simplicity make our method a straightforward strategy to construct gem-difluoroalkenes bearing various functional groups, and a powerful strategy for incorporating a gem-difluoroalkene moiety into natural products and drug molecules.
Keywords: photoredox reaction; defluorination; silylation; difluoroalkenes; silyl radicals; late-stage modification